Regulasi diri sebagai mediator interaksi mindfulness dan prokrastinasi akademik - Dzakiah, Shofa; Widyasari, Pratiwi (Faculty of Psychology Universitas 17 Agustus 1945 Surabaya, 2021)
AbstractAcademic procrastination in college students is a common phenomenon, although procrastination’s negative impacts were well known. This study aimed to examine the role of self-regulation in mediating the correlation between mindfulness and academic procrastination. Data were collected by distributing online questionnaires to college students from various universities in Indonesia (n = 305). The sampling technique used was convenience sampling. Instruments used in the research were the Mindfulness Attention and Awareness Scale, the Short form of Self-regulation Questionnaire, and the Academic Procrastination Scale. The regression and mediation analyses were held. Results showed that self-regulation partially mediated the correlation between mindfulness and academic procrastination. Increasing in dispositional mindfulness helps college students regulate themselves, thereby reducing the tendency to procrastinate. The implications and limitations of the study and suggestions for further research are discussed.Keywords: academic procrastination; college students; mindfulness; self-regulation.AbstrakProkrastinasi akademik pada mahasiswa merupakan fenomena yang umum terjadi, meskipun dampak negatif prokrastinasi telah banyak diketahui. Penelitian ini bertujuan menguji peran regulasi diri dalam memediasi hubungan antara mindfulness dan prokrastinasi akademik. Pengambilan data dilakukan melalui penyebaran kuesioner secara daring kepada mahasiswa di berbagai perguruan tinggi di Indonesia (n=305). Teknik sampling yang digunakan adalah convenience sampling. Penelitian ini menggunakan alat ukur Mindfulness Attention and Awareness Scale, Short Self-Regulation Questionnaire, dan Academic Procrastination Scale. Hasil uji regresi dan uji mediasi menunjukkan regulasi diri memediasi korelasi antara mindfulness dan prokrastinasi akademik secara parsial. Peningkatan kondisi kesadaran pada mindfulness membantu mahasiswa meregulasi dirinya, sehingga mengurangi kecenderungan untuk melakukan prokrastinasi akademik. Implikasi dan keterbatasan penelitian serta saran untuk penelitian selanjutnya didiskusikan.Kata kunci: mahasiswa; mindfulness; prokrastinasi akademik; regulasi diri.